Reflections on rationality, utility, university, mass culture and unsustainable society - Jerzy Śleszyński (Central European Economic Journal (CEEJ), 2021)
This paper is an expression of gratitude, remembrance and honour the jubilee of Prof. Tomasz çZylicz. As I have been invited to write a paper for a special issue of the CEEJ journal, I sincerely wanted to express regarding my friendship and my research that have been binding me with Tomasz in my more than 40-year work in the Faculty of Economic Sciences, University of Warsaw. Our cooperation was varied and rich including joint articles, research projects and our work for the Ministry of the Environment. In this paper, after friendly acknowledgment, I decided to propose my polemical answer to the paper 'Is reason valued now?' written by Tomasz. The subject of my reply is primarily the rationality in general and in the institution of university in the context of teaching and practicing science, including first of all economics and ecological economics. The method applied in this paper is my descriptive and polemical reference to Tomasz's theses with the analytical use of literature, both classics and very current references. The basic topic of the paper focuses on the fact that modernity continues in an increasingly inertial movement towards mass culture and is dominated by three criteria in this mechanism namely usefulness, non-exclusion and accessibility. I analyse these three fetishes in our dynamic times and with particular emphasis on their negative role in academic education. In my conclusions I categorically state that scientific knowledge and education, perfectly represented by universities, were formed and developed in an alliance with usefulness and utility, but never only thanks to them and never only for them.
Keywords: A12; A20; B40; 330; education; mass culture; rationality; utility; university